Parental Misconduct in Child Education: A Legal Perspective on Parents’ Reactions to School Discipline in Indonesia - Salim, Agus; Yusoh, Ruslan (Sabtida, 2025)
This article examines parental misconduct in the context of child education, specifically focusing on legal perspectives regarding parents’ reactions to school discipline in Indonesia. The study seeks to analyze how parental interventions, whether excessive or lacking, can disrupt the effectiveness of school disciplinary processes, potentially contravening principles enshrined in national child protection laws. By reviewing statutory regulations such as Law No. 35/2014 on Child Protection and corresponding Ministerial Regulations, this research explores the boundaries of parental rights and responsibilities when responding to disciplinary measures imposed by schools. The methods applied center on normative legal analysis and comparative studies of recent case examples in Indonesian schools. The results reveal ongoing tension between parental authority and school autonomy, highlighting frequent legal ambiguities that complicate child-friendly disciplinary enforcement. The article concludes that balanced cooperation between schools and parents, rooted in legal clarity and mutual respect, is essential for effective child discipline and educational safety in Indonesia.